Triatomine (Hemiptera: Rediviidae) behavioral aspects: Chagas disease vectors - Castillo, Diana; Wolff, Marta (Biomedica, 2000)
The article presents an updated review of triatomines, Chagas disease vectors, with respect to the taxonomy of presently known species, as well as those located in dwellings in Colombia, and the group's life cycle, including population size, theirspreading mechanisms, and anthropicfactors which are forcing domiciliation habits among them. We also cal1 attention on the epidemioloqical consequences resulting from such changes. Trypanosoma cruziin Colombia affects 3.3% of thépopulation, from which around 10% is in risk of qettinq infected. Three bioloqical components act in this infectious disease: the protozoa T. cruzi, the tryatomine Reduviidae vectoránd the vertebrate reservoir. Although the Triatomine is originally a sylvatic insect, the alteration of its natural habitat, including forest devastation, housing construction with palm leaves and indiscriminate hunting, has changed substantially their behaviour. Thus, Triatomines are invading households and there are already signs of domiciliation which are forcing important changes in the vector-host-parasite behaviour and, consequently, in the disease itself.